Early protein expression profile in bronchoalveolar lavage fluid and clinical outcomes in primary graft dysfunction after lung transplantation. (8th April 2020) - Frick, Anna E; Verleden, Stijn E; Ordies, Sofie; Sacreas, Annelore; Vos, Robin; Verleden, Geert M; Vanaudenaerde, Bart M; Claes, Sandra; Schols, Dominique; Van Raemdonck, Dirk E; Neyrinck, Arne P
Abstract: OBJECTIVES: Primary graft dysfunction (PGD) remains a major post-transplant complication and is associated with increased morbidity and mortality. Mechanisms evoking PGD are not completely clear, but inflammation plays a central role. We investigated the association between PGD and inflammatory proteins present in immediate postoperative bronchoalveolar lavage. METHODS: All double-lung recipients transplanted at our institution from 2002 to 2018 were included in our study. We retrospectively selected 80 consecutive lung transplant recipients with different PGD grades ( n = 20 for each PGD grades 0–1 to 2–3). In bronchoalveolar lavage performed within the first 24 h after donor aortic cross-clamping following lung transplantation, concentrations of 30 cytokines, chemokines and growth factors were assessed by enzyme-linked immunosorbent assay (ELISA) and correlated with donor and recipient demographics and outcomes. For analysis, 2 groups were defined: 'mild' PGD (grade 0–1) and 'severe' PGD (grades 2–3). RESULTS: Significant differences between mild and severe PGD were found in 8 biomarkers [interleukin (IL)-6, IL-10, IL-13, eotaxin, granulocyte colony-stimulating factor, interferon γ, macrophage inflammatory protein 1α, surfactant protein D (SP-D); P < 0.05]. Increased IL-10 and IL-13, but none of the other proteins, were associated with short-term outcome (longer time to extubation; P = 0.005 and P < 0.0001; increased intensive care unit stay; P = 0.012 and P < 0.0001; and hospital stay; P = 0.041 and P = 0.002). There were no significant differences in donor and recipient characteristics between the groups. CONCLUSIONS: Expression profiles of key inflammatory mediators in bronchoalveolar lavage fluid differed significantly between lung transplant recipients with severe versus mild PGD and correlated with clinical outcome variables. Further research should focus on the early mechanisms leading to PGD.